Kinematics of Hitting in Youth Baseball: Implications for Skill Development - Bordelon, Nicole; Fava, Anthony; Friesen, Kenzie B.; Crotin, Ryan L; Oliver, Gretchen D (International Journal of Sports Medicine, 2024)
This study compared lower extremity, trunk, and upper extremity kinematics between tee and front toss hitting in youth baseball athletes. Twenty youth baseball athletes (14.3±2.9 yrs) performed three maximal effort swings off front toss and tee. Kinematic data were collected during the preparatory and acceleration phases. Lower extremity, trunk, and upper extremity kinematics were compared between tee and front toss hitting using 1-dimensional statistical parametric mapping (SPM). There was a significant difference in trunk kinematics between tee and front toss during the preparatory phase (p=.001); the trunk rotated more toward the back side when hitting off a tee compared to front toss (p<0.001). There was also a significant difference in trunk kinematics between tee and front toss for 67% of the acceleration phase; the trunk rotated more towards the back side from 0 to 67% when hitting off the tee (p<0.001). Significant differences were found in trunk kinematics between tee and front toss hitting in youth baseball players, where the trunk is less rotated toward the pitcher in the tee than in the front toss. Coaches utilize various training modalities to enhance hitting performance; however, differences in trunk kinematics should be considered between modalities when developing fundamental hitting techiques in youth baseball athletes.
Keywords: batting; lower extremity; mechanics; trunk; upper extremity